A Portrait of Pacing Profile of Cross-Country Skiers in the Vasaloppet 2004–2017 - Nikolaidis, Pantelis Theodoros; Villiger, Elias; Rosemann, Thomas; Knechtle, Beat (International Journal of Sports Medicine, 2018)
The aim of the study was to examine the effect of performance group by race time (10 groups;<3 h, 3–4 h, and so on up to>12 h) on pacing in women (n=19,465) and men (n=164,454) finishers in the ‘Vasaloppet’ cross-country (XC) skiing race from 2004 to 2017. The speed in the fastest and slowest split was analysed as a percentage of the mean race speed and pacing was defined as the difference (%) between the fastest and slowest split. Women had a larger pace range than men (44.0±10.6% versus 41.1±12.5%, respectively, p<0.001, d=0.25). An almost perfect relationship between performance group and pacing was observed in women (r=0.900, p<0.001) and men (r=0.908, p<0.001). A large main effect of performance on pacing was observed in women (p<0.001, η2=0.292), where the smaller range was in the<4 h group (22.8±3.3%) and the largest in the 10–11 h group (49.2±9.9%). In men, the corresponding values were 21.6±2.2% (<3 h group) and 51.6±11.2% (10–11 h group; p<0.001, η2=0.474). Based on these findings, it was concluded that fast XC skiers had relatively the most even pacing and pacing became less even with decreasing performance. This information is of practical value for coaches working with XC skiers to develop optimal sex- and performance-tailored pacing strategies.
Keywords: endurance exercise; gender; race speed; skiing; sport performance; winter sport